IMPROVING THE TRANSPORT AND LOGISTICS SYSTEM FOR SMALL BUSINESS DEVELOPMENT - Ismoilov Narimonjon No‘monjon o‘g‘li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The development of small businesses can be significantly enhanced through the improvement of transport and logistics systems. In modern economic conditions, supply chains play a crucial role in production, trade, and service delivery. Therefore, the efficiency of transport logistics has become an important factor for small business performance. The study examines transport logistics operations in production, trade, and service sectors, including freight and passenger transport as well as logistics center activities. The research highlights the relevance of improving logistics infrastructure to support sustainable small business growth.